Psychometric investigation of benefit finding among long-term cancer survivors using the Medical Expenditure Panel Survey. (February 2016) - Jones, Salene M.W.; Ziebell, Rebecca; Walker, Rod; Nekhlyudov, Larissa; Rabin, Borsika A.; Nutt, Stephanie; Fujii, Monica; Chubak, Jessica
Abstract: Purpose: Benefit finding has been shown to be beneficial for people with cancer and may be an indication that one is coping adequately with the stress of cancer. This study evaluated the psychometric properties of a four-item benefit finding measure from the cancer survivorship supplement of the Medical Expenditure Panel Survey (MEPS). Methods: Long-term survivors (5–10 years post-diagnosis) of breast, prostate, colorectal or lung cancer or melanoma (n = 594) completed the MEPS cancer supplement survey in 2013. Four items asked about benefit finding after the cancer: stronger person, coping better, positive changes and having healthier habits. Information on sociodemographics, disease and activity limitations after the cancer was also collected. We examined factor structure, reliability (Kuder-Richardson 20) and validity. Results: The four benefit finding items did not appear to measure one factor. Three of the benefit finding items (stronger person, coping better, positive changes) were related to gender, receipt of chemotherapy and activity limitations but not cancer stage, time since diagnosis or income. Having healthier habits was unrelated to any sociodemographic or disease variable. Conclusions: Three of the items (stronger person, coping better, positive changes) appeared to have validity as they were related to variables that literature has shown are related to benefit finding. However, having healthier habits is likely measuring a separate but related construct. This short instrument may be used in future studies assessing benefit finding post cancer; however, the four items should be analyzed separately. Highlights: We examined measurement properties of 4 benefit finding items from the MEPS survey. The items were related to factors associated with benefit finding showing validity. Factor analysis suggested each item should be analyzed separately.